Acoustic measurement in a rectangular bubble column to determine bubble size and interfacial area for aqueous solutions of ethylene glycol - Verma A.K.; Nayak C. (My University, 2025)
Bubble sizes in bubble column affect the bubble induced mixing of phases, interfacial area and transfer processes. Acoustic technique is used to measure bubble size distribution in a rectangular bubble column of cross section 0.2m x 0.02m for air sparged into water and aqueous solutions of ethylene glycol. Five condenser mikes at intermediate distance of 0.05 m measured above the distributor plate were used to find out the variation of bubble size as the bubbles move up. Sauter-mean bubble diameter and specific interfacial area were estimated from bubble size distribution at several superficial air velocity, static bed height, distance above the distributor plate and ethylene glycol concentration. The BSD exhibited mono-modal distribution and indicated non-uniform homogeneous bubbling regime. Sauter-mean bubble diameter is independent of superficial gas velocity, static bed height and concentration of EG, although, the values were higher than that for air-water system. Sauter-mean bubble diameter decreases as the bubbles move up indicating bubble breakup to take place once the bubbles leave the sparger. The value of interfacial area increases as the static bed height decreases and distance above the distributor plate increases. For air-ethylene glycol solution the values of specific interfacial area are about 200% higher than that observed in case of air-water system. The acoustic technique may be used to measure local values of bubble sizes and specific interfacial area. © BEIESP.